PEMBERDAYAAN IBU DHARMA WANITA DALAM PENCEGAHAN DINI KANKER SERVIKS - Oktavianisya, Nelyta (JPMAS : Jurnal Pengabdian Masyarakat, 2026)
Cervical cancer could be detected early through screening, however public awareness, especially women, is still lacking in carrying out early examinations. The aim of this activity is to empower member of Dharma Wanita in early prevention of Cervical Cancer. The method used is socialization and the formation of member candidate on early cervical cancer prevention . The media used to deliver health education material are leaflets, PowerPoint, videos. The team collaborated with Fortuna Sumenep laboratory staff to carry out pap smear tests. This community services were carried out in Kecamatan Bluto , especially for the member of Dharma Wanita in Bluto at November 2022 until April 2023. There are several stages of activities namely situation analysis, health education, the formation of member candidate on early cervical cancer prevention and evaluation. The results of this activity had a good impact, the knowledge level of participants increased to 87%, and 54.4% of respondents were willing to undergo a pap smear examination (25 people).